U.S. climate policy uncertainty shocks and the growth in renewable energy production - Payne, James E.; Nazlioglu, Saban; Koncak, Ahmet; Ewing, Bradley T. (Journal of commodity markets, 2025)
Investment in renewable energy production has been subject to swings in the U.S. policy stance on climate change creating uncertainty. Determining how and to what extent the renewable energy sector responds to climate policy uncertainty is relevant to understanding the energy transition from fossil fuels to renewables. This study examines the relationship between the growth in renewable energy production and its sub-components and climate policy uncertainty while accounting for oil price uncertainty and the growth in oil prices, industrial production, and carbon emissions, respectively. Utilizing generalized impulse response analysis within a vector autoregressive model framework, we find that total renewable energy production responds negatively to shocks to climate policy uncertainty but exhibits only a small positive response to oil price uncertainty. Further examination of renewable energy production by its sub-components (i.e., hydropower, biomass, geothermal, wind, and solar) shows that the time path responses to uncertainty shocks differ by sub-component. The findings suggest that policies to facilitate an energy transition by treating renewables similarly may not have the desired effects and thus should be tailored to individual sub-components to achieve targeted goals for renewable energy production.